Generation of mega-gauss axial and azimuthal magnetic fields in a solid plasma by ultrahigh intensity, circularly polarized femtosecond laser pulses - Anandam Choudhary; Laxman Prasad Goswami; C. Aparajit; Amit D. Lad; Ameya Parab; Yash M. Ved; Trishul Dhalia; Amita Das; G. Ravindra Kumar (Fundamental Plasma Physics)
The interaction of intense linearly polarized (LP) femtosecond laser pulses with solids is known to generate azimuthal magnetic fields, while circularly polarized (CP) light has been shown to create axial fields. We demonstrate through experiments and particle-in-cell simulations that circularly polarized light can generate both axial and azimuthal fields of comparable magnitude in a plasma created in a solid. Angular distributions of the generated fast electrons at the target front and rear show significant differences between the results for the two polarization states, with circular polarization enforcing more axial confinement. The measurement of the spatial distribution of both types of magnetic fields captures their turbulent evolution.